2003
DOI: 10.1007/s11357-003-0003-x
|View full text |Cite
|
Sign up to set email alerts
|

Copper deficiency: A potential model for determining the role of mitochondria in cardiac aging

Abstract: Heart mitochondria experience age-related declines in cytochrome c oxidase (CCO) activity and increases in the generation of reactive oxygen species (ROS) that may contribute to loss of cardiac function and the development of disease that occur with advancing age. In a manner similar to aging, copper deficiency also suppresses heart CCO activity and has cardiovascular consequences related to increased peroxidation. Food restriction is often used as a tool to study oxidative mechanisms of aging and the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Cytochrome c activity is positively correlated with copper concentrations in copper-deficient and copper-sufficient rats, indicating another mechanism through which copper concentrations affect mitochondrial function. 41 A decline in cytochrome c oxidase (CCO) activity is characteristic of the ageing heart, and copper deficiency causes the same phenomenon. Reduced CCO activity in turn leads to cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytochrome c activity is positively correlated with copper concentrations in copper-deficient and copper-sufficient rats, indicating another mechanism through which copper concentrations affect mitochondrial function. 41 A decline in cytochrome c oxidase (CCO) activity is characteristic of the ageing heart, and copper deficiency causes the same phenomenon. Reduced CCO activity in turn leads to cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Copper deficiency in experimental animals can be used as a model for studying the place of mitochondrial function in the ageing heart. 41 Mitochondria of copper-deficient rats consume oxygen at a significantly lower rate than those of copper-sufficient rats; they have a lower membrane potential and an altered ATP synthase complex, indicating lower rates of energy production. 42 …”
Section: Introductionmentioning
confidence: 99%
“…Although copper is crucial for cytochrome oxidase function, the transporters and regulators of mitochondrial copper are unknown. In rats, a copper-deficient diet caused a 74% decrease in CCO and increased manganese superoxide dismutase (MnSOD) and GPX in isolated heart mitochondria [150,151]. This is an indirect indication that mitochondrial ROS production was increased [151].…”
Section: Coppermentioning
confidence: 99%
“…In rats, a copper-deficient diet caused a 74% decrease in CCO and increased manganese superoxide dismutase (MnSOD) and GPX in isolated heart mitochondria [150,151]. This is an indirect indication that mitochondrial ROS production was increased [151]. Moreover, specifically cardiac mitochondrial ETC function was compromised in copper-deficient rats [55].…”
Section: Coppermentioning
confidence: 99%
“…Cu is an essential component of the mitochondrial complex IV (cytochrome C oxidase) [ 10 , 11 ]. In Johnson and Newman’s study (2003), a Cu-deficient diet in rats resulted in a decrease in cytochrome C oxidase, an increase in manganese superoxide dismutase (MnSOD), and glutathione peroxidase (GPX) in isolated cardiac mitochondria [ 22 ]. Chen et al study (2002) demonstrated impaired cardiac mitochondrial respiration in rats with a Cu-deficient diet [ 23 ].…”
Section: Introductionmentioning
confidence: 99%